Cytomorphological diagnosis of pilomatricoma in an unusual location - Dr. Nehal Ahmad; Dr. Mohd. Jaseem Hassan; Dr. Zeeba S Jairajpuri; Dr. Sabina Khan; Dr. Rubeena Naz; Dr. Sujata Jetley (Tropical Journal of Pathology and Microbiology, 2018)
Pilomatricomaisa benign skin adnexal tumor that is derived from hair matrix. Pilomatricomas usually present in children and adolescents but can occur at any age. Pilomatricomas are generally asymptomatic and found mainly in the head and neck area. Upper extremities not a common site for this lesion. It israrely identified on the chest, trunk, or lower extremities. They areeasily diagnosed on histology due to their typical histological features but diagnosis in cytology is generally difficult as the features may mimic other skin lesions and leads to misdiagnosis.Here we describe a case of pilomatricoma of left arm in a 25 year old male, which was diagnosed on cytology. The cytological smears were cellular and consist of aggregates of anucleate squames, basaloid cells and shadow cells. Subsequent histopathologyof the excised lesion confirmed the diagnosis of Pilomatricoma. Through thisreport we highlight the cytomorphological features that helps us in arriving the correct diagnosis of Pilomatricomaon Fine needle aspiration cytology (FNAC) smears.